1982
DOI: 10.1063/1.444023
|View full text |Cite
|
Sign up to set email alerts
|

Raman and x-ray investigations of ice VII to 36.0 GPa

Abstract: Raman data for ice VII to 30 GPa and x-ray lattice parameters to 36 GPa, all at room temperature, are presented and discussed. Both the Raman OH-stretching peak frequency (Δv̄) and the edge distance of the body-centered cubic unit cell (a) decrease at a decreasing rate with pressure rise. The OH peak frequency is found to be virtually linear in the nearest-neighbor O–O distance (rOO) between about 2.5 and 2.9 Å. However, the data can also be fitted with a slight cubic dependence, which when extrapolated, gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 16 publications
5
42
0
Order By: Relevance
“…The hydrocarbon was clearly identified as methane based on the sharp band at 2,972 cm Ϫ1 , matching the position of bulk methane at this pressure (20). The broad feature near 3,200 cm Ϫ1 is caused by O-H stretching in ice VII (21). This sample exhibited considerable heterogeneity; Raman measurements of laser-heated experiments were typically challenging because after heating the samples were finegrained and fluorescent, and a layer of opaque material across the diamond surface often obscured the interior of the sample chamber from optical measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrocarbon was clearly identified as methane based on the sharp band at 2,972 cm Ϫ1 , matching the position of bulk methane at this pressure (20). The broad feature near 3,200 cm Ϫ1 is caused by O-H stretching in ice VII (21). This sample exhibited considerable heterogeneity; Raman measurements of laser-heated experiments were typically challenging because after heating the samples were finegrained and fluorescent, and a layer of opaque material across the diamond surface often obscured the interior of the sample chamber from optical measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the convenience of working at room temperature, there have been numerous investigations of ice VII by Raman scattering, 6,9,27,41 infrared absorption, 7,24,25,46 -49 xray diffraction 9,41,42,50 -54 and neutron diffraction up to 26 GPa. 55,56 Owing to the pressure-temperature shape of the stability domain of ice VIII, very high-pressure investigations must be performed at least down to 100 K. With Raman scattering, apart from the investigation performed in the Geophysical Laboratory (Carnegie Institute) for determining the VII-X transition, where the general behaviour of the various modes of ice VIII was given to 62 GPa at 20 K, 23 currently only partial data are available.…”
Section: Introduction Overview On the Experimental Data On VII And Viiimentioning
confidence: 99%
“…Despite considerable discussion in the literature [4][5][6][7][8][9], there is to date no compelling direct evidence for the existence of ice X. Experimentally, Raman spectra of ice VIII up to 50 GPa at 100 K demonstrate the appearance of a new band above 40 GPa [4] which could reflect such a transition; and Brillouin scattering studies up to 67 GPa at 300 K also give an indication of a transition at 44 GPa from an anomaly in the behavior of the longitudinal sound velocity [5]. Earlier work based on extrapolation of Raman spectra from lower pressures at room temperature also suggested that a symmetric hydrogen-bond structure might form in ice VII at pressures of about 75 ± 20 GPa [6].…”
mentioning
confidence: 99%